Tutorial on fiber-based sources for biophotonic applications - Taylor,JR (Journal of Biomedical Optics, 2016)
Fiber-based lasers and master oscillator power fiber amplifier configurations are described. These allow spectral versatility coupled with pulse width and pulse repetition rate selection in compact and efficient packages. This is enhanced through the use of nonlinear optical conversion in fibers and fiber-coupled nonlinear crystals, which can be integrated to provide all-fiber pump sources for diverse application. The advantages and disadvantages of sources based upon supercontinuum generation, stimulated Raman conversion, four-wave mixing, parametric generation and difference frequency generation, allowing spectral coverage from the UV to the mid-infrared, are considered.